A rare case report on cervical pregnancy - Jariwala, Sherebanu Z.; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cervical pregnancy is a rare type of ectopic pregnancy and it represents <1% of all ectopic pregnancies. Tubal ectopic, Interstital, caesarean scar pregnancy, cornual, ovarian, Intramural are other types of ectopic pregnancy. Timely diagnosis and Treatment are key to management any type of ectopic pregnancy. Cervical ectopic pregnancy is the implantation of blastocyst in the intracervical canal. Cervical pregnancy are high risk cases as they may present with an unexpected life-threatening hemorrhage secondary to the erosion of cervical blood vessels, which may require hysterectomy to save the patient. Here is case of 22yr old primi patient with 6 weeks and 2 days of cervical ectopic pregnancy planned for dilatation and evacuation followed by medical management span; Improved ultrasound resolution and earlier detection of these pregnancies have led to the development of more conservative treatments that attempt to limit morbidity and preserve fertility. <!–/data/user/0/com.samsung.android.app.notes/files/clipdata/clipdata_bodytext_240326_212744_601.sdocx–>